Application of artificial intelligence in Fault Detection and Isolation of uncertain parameter systems. (3rd December 2009) - Bouabdallah, Salma Bouslama; Tagina, Moncef
In this article, two original intelligent methods for Fault Detection and Isolation (FDI) affecting sensors and actuators in case of bond graph modelled uncertain parameter systems are proposed. First, a fuzzy approach based on residual processing is proposed for FDI offline, binary approach and fuzzy approach are compared through an illustrative example. Secondly, a multilayer perceptron trained with resilient backpropagation algorithm is proposed for FDI online.